Analysis of Feeding Habits of Silver Barb (Barbonymus gonionotus) in The Waters of Way Sekampung Dam, Pagelaran District, Pringsewu Regency, Lampung - Atika Juliarti; Hani Wijayanti Maharani; Rizha Bery Putriani (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2025)
The freshwater ecosystem of Way Sekampung Dam in Pagelaran District, Pringsewu Regency, Lampung Province, was selected as the research site due to its fertile environment, rich biodiversity, and high potential for aquatic biota studies. Silver barb (Barbonymus gonionotus), known for their adaptability and herbivorous feeding habits, were the focus of this study, which aimed to investigate their natural food preferences as a basis for sustainable fish resource management. Although primarily herbivorous, silver barb were also known to consume supplementary food such as bran and organic waste. The research was conducted from September to December 2024. Data analysis included the Index of Preponderance (IP), niche breadth, and food overlap. Results showed that silver barb predominantly consumed plant litter and phytoplankton, specifically Gyrosigma fasciola, Rhabdonema arcuatum, Oscillatoria, and Closterium. Food overlap between male and female fish remained low throughout the study, with values of 0.1051 at the beginning and 0.0851 at the end of the sampling period. This indicated differing food preferences between sexes during the transition months. Overall, the findings highlighted how seasonal dynamics and ecological variability influenced the feeding behavior and resource use of silver barb in the Way Sekampung Dam.